Extractive industry and the politics of manhood in Nigeria's Niger Delta: a masculinity perspective of gender implication of resource extractivism. Issue 4 (2nd October 2019) - Ashamole, Darlington C.
ABSTRACT: Using an empirical case study focusing on the oil-rich region of Nigeria's Niger Delta, this paper contributes to discourse on the gender and environmental politics of resource extractivism. It examines the ways in which oil resource extraction and other activities undertaken by oil multinationals operating in the Niger Delta have impacted on men and masculinities by interfering with the process of becoming a man and triggering what the paper terms the 'frustration of unrealised masculinity' or the 'frustration of failed manhood', which the young men affected tend to express through violence. The paper further identifies the resulting violence as one of the implications of the construction of masculinity in the Niger Delta and elsewhere based on socio-economic achievements – namely marriage or breadwinning for a family and financial independence. The study uses a qualitative research paradigm involving purposive sampling and semi-structured interviews to enable direct engagement with the research population.